Expression Analysis of WRKY Transcription Factor Genes in Response to Abiotic Stresses in Horsegram (Macrotyloma uniflorum (Lam.) Verdc.) - Kiranmai, Kurnool; Gunupuru, Loknatha R.; Nareshkumar, Ambekar; Reddy, Vennapusa A.; Lokesh, Uppala; Pandurangaiah, Merum; Venkatesh, Boya; Kirankumar, Tanguturi V.; Sudhakar, Chinta (Scientific Research Publishing, 2016)
Drought and salt stress are two major environmental constraints that limit the productivity of agriculture crops worldwide. WRKY transcription factors are the plant-specific transcription factors that regulate several developmental events and stress responses in plants. The WRKY domain is defined by a 60-amino acid conserved sequence named WRKYGQK at N-terminal and a Zinc Finger-like motif at the C-terminal. WRKY genes are known to respond several stresses which may act as negative or positive regulators. The function of most of the WRKY transcription factors from non-model plants remains poorly understood. This investigation shows the expression levels of eight WRKY transcription factor genes from horsegram plant under drought and salt stress conditions. The increase in mRNA transcript levels of WRKY transcription factor genes was found to be high in drought stressed plants compared to salt-stressed plants. The levels of MDA which indicates the lipid peroxidation were less in drought stress. More ROS is produced in salt stress conditions compared to drought. The results show that the expression of WRKY transcription factors in drought stress conditions is reducing the adverse effect of stress on plants. These results also suggest that, during abiotic stress conditions such as drought and salt stress, WRKY transcription factors are regulated at the transcription level.
Keywords: Drought; Salt; Lipid Peroxidation; Plant Abiotic Stress; qRT-PCR; Reactive Oxygen Species; WRKY